Women’s Economic Empowerment in Uganda: Inequalities and Implications - Barungi, Mildred (Economic Policy Research Centre, 2019)
Women’s Economic Empowerment (WEE) is a necessary condition for sustainable development and pro-poor growth. It increases women’s access to economic resources and opportunities. Although, there are laws, policies and programmes supporting Women’s Economic Empowerment in Uganda, evidence from the 2017 Baseline Survey of Perceptions on Violence Against Women, Women’s Economic Empowerment and Women’s Political Participation and Leadership report of the NGPSS 2017; reveals remarkable gender inequalities. Disproportionately more women than men are disadvantaged in terms of education attainment and so they lack the requisite knowledge and skills for capturing decent employment opportunities. Also, more men than women are opposed to females owning and inheriting land, and being part of the key decision-making organs on land and other property. This brief recommends second chance education for the out-of-school females, popularisation and enforcement of land policy provisions, and targeted rolling out of Women Empowerment programmes.